Prevalence and causes of vision loss in sub-Saharan Africa in 2015: magnitude, temporal trends and projections. Issue 12 (30th March 2020) - Naidoo, Kovin; Kempen, John H; Gichuhi, Stephen; Braithwaite, Tasanee; Casson, Robert J; Cicinelli, Maria Vittoria; Das, Aditi; Flaxman, Seth R; Jonas, Jost B; Keeffe, Jill Elizabeth; Leasher, Janet; Limburg, Hans; et al.
Abstract : Background: This study aimed to assess the prevalence and causes of vision loss in sub-Saharan Africa (SSA) in 2015, compared with prior years, and to estimate expected values for 2020. Methods: A systematic review and meta-analysis assessed the prevalence of blindness (presenting distance visual acuity <3/60 in the better eye), moderate and severe vision impairment (MSVI; presenting distance visual acuity <6/18 but ≥3/60) and mild vision impairment (MVI; presenting distance visual acuity <6/12 and ≥6/18), and also near vision impairment (<N6 or N8 in the presence of ≥6/12 best-corrected distance visual acuity) in SSA for 1990, 2010, 2015 and 2020. In SSA, age-standardised prevalence of blindness, MSVI and MVI in 2015 were 1.03% (80% uncertainty interval (UI) 0.39–1.81), 3.64% (80% UI 1.71–5.94) and 2.94% (80% UI 1.05–5.34), respectively, for male and 1.08% (80% UI 0.40–1.93), 3.84% (80% UI 1.72–6.37) and 3.06% (80% UI 1.07–5.61) for females, constituting a significant decrease since 2010 for both genders. There were an estimated 4.28 million blind individuals and 17.36 million individuals with MSVI; 101.08 million individuals were estimated to have near vision loss due to presbyopia. Cataract was the most common cause of blindness (40.1%), whereas undercorrected refractive error (URE) (48.5%) was the most common cause of MSVI. Sub-Saharan West Africa had the highest proportion of blindness compared with the other SSA subregions. Conclusions: Cataract and URE, two of the major causes of blindness and vision impairment, are reversible with treatment and thus promising targets to alleviate vision impairment in SSA.